2016
DOI: 10.1111/jgs.14403
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Initiation and Discontinuation of Antidementia Drugs by Medicare Beneficiaries

Abstract: BACKGROUND/OBJECTIVES Clinical practice guidelines support using acetylcholinesterase inhibitors (AChEIs) and memantine to treat dementia, but conflicting evidence of effectiveness and frequent side effects limit use in practice. We examined racial/ethnic differences in initiation and time to discontinuation of antidementia medication in Medicare beneficiaries. DESIGN Retrospective cohort study. SETTING Secondary analysis of 2009/2010 enrollment, claims, and Part D prescription data for a 10% national samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 45 publications
(83 reference statements)
0
41
0
Order By: Relevance
“…These include a large USA study, in which people from Black and Hispanic ethnic groups were more likely to discontinue antidementia medication, relative to people from White ethnic groups. 9 In a large Australian care homes study, antidementia medication was initiated earlier in residents who spoke English as a first language. 8 There are international variations in subsidisation of anti-dementia medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a large USA study, in which people from Black and Hispanic ethnic groups were more likely to discontinue antidementia medication, relative to people from White ethnic groups. 9 In a large Australian care homes study, antidementia medication was initiated earlier in residents who spoke English as a first language. 8 There are international variations in subsidisation of anti-dementia medications.…”
Section: Discussionmentioning
confidence: 99%
“…7 Large studies in Australia and the USA have concluded that minority ethnic groups access anti-dementia treatments later 8 or are more likely to discontinue. 9 We defined good quality mental healthcare as: access to cholinesterase inhibitors or memantine (anti-dementia drugs) to treat dementia symptoms where they are indicated; low antipsychotic, hypnotic, and anxiolytic medication use, due to the associated risks of cognitive decline, falls, cerebrovascular events and death; 10 and low use of anticholinergic drugs, which are associated with worse cognition and quality of life. 11 The Choosing Wisely recommendations and other guidelines advocate limiting initiation and duration of antipsychotic prescribing for behavioural and psychological symptoms of dementia (BPSD) as far as possible.…”
Section: Introductionmentioning
confidence: 99%
“…This variable was developed by the CMS based on valid disease classification and procedure codes from Medicare claims 15 and has been used extensively in literature. 14,[16][17][18][19][20][21][22][23][24][25][26][27][28] Previous studies demonstrate a 95% specificity using Medicare claims and a 79% sensitivity among continuous enrollees in Medicare fee-or-service using this definition. 29,30 Then, we selected those who filled at least 1 prescription for an antidementia drug (donepezil, rivastigmine, galantamine, or memantine) after the AD diagnosis (n ¼ 73 642).…”
Section: Data Source and Study Populationmentioning
confidence: 93%
“…Not recognizing early changes in cognitive function as a sign of ADRD may contribute to Hispanics experiencing declines in memory for a longer period of time before being diagnosed with ADRD [19] and having more severe symptoms when ADRD is diagnosed compared to non-Hispanic whites [20,21]. Some [22], but not all [23] studies have reported that Hispanics who have been diagnosed with ADRD are less likely than non-Hispanic whites to be taking medications for ADRD symptoms. The more severe ADRD symptoms and less treatment of symptoms among older Hispanics may contribute to increased healthcare utilization in this population.…”
Section: Introductionmentioning
confidence: 99%